Impact of Raltegravir or Efavirenz on Cell-Associated Human Immunodeficiency Virus-1 (HIV-1) Deoxyribonucleic Acid and Systemic Inflammation in HIV-1/Tuberculosis Coinfected Adults Initiating Antiretroviral Therapy. (11th January 2020) - Delagreverie, Héloïse M; Bauduin, Claire; De Castro, Nathalie; Grinsztejn, Beatriz; Chevrier, Marc; Jouenne, Fanélie; Mourah, Samia; Kalidi, Issa; Pilotto, Jose Henrique; Brites, Carlos; Tregnago Barcellos, Nemora; Amara, Ali; et al.
Abstract: Background: In view of the fast viremia decline obtained with integrase inhibitors, we studied the respective effects of initiating efavirenz (EFV) or raltegravir (RAL)-based antiretroviral therapy (ART) regimens on human immunodeficiency virus (HIV)-1 deoxyribonucleic acid (DNA) levels and inflammation biomarkers in the highly inflammatory setting of advanced HIV-1 disease with tuberculosis (TB) coinfection. Methods: We followed cell-associated HIV-1 DNA, high-sensitivity C-reactive protein (hsCRP), interleukin 6 (IL-6), soluble CD14 and D-Dimer levels for 48 weeks after ART initiation in the participants to the ANRS12-180 REFLATE-TB study. This phase II open-label randomized study included ART-naive people with HIV and TB treated with rifampicin to receive RAL 400 mg twice daily (RAL400), RAL 800 mg twice daily (RAL800) or EFV 600 mg QD with tenofovir and lamivudine. Results: In 146 participants, the median (interquartile range [IQR]) week (W)0 HIV-1 DNA level was 4.7 (IQR, 4.3–5.1) log10 copies/10 6 CD4 +, and the reduction by W48 was −0.8 log10 copies/10 6 CD4 + on EFV, −0.9 on RAL400, and −1.0 on RAL800 ( P = .74). Baseline median (IQR) hsCRP, IL-6, sCD14, and D-Dimer levels were 6.9 (IQR, 3.3–15.6) mg/L, 7.3 (IQR, 3.5–12.3) pg/mL, 3221 (IQR, 2383–4130) ng/mL, and 975 (IQR, 535–1970) ng/mL. All biomarker levels decreased over the study: the overall W0–W48 mean (95% confidence interval) fold-change on ART was 0.37 (IQR, 0.28–0.48) for hsCRP, 0.42 (IQR, 0.35–0.51) for IL-6, 0.51 (IQR, 0.47–0.56) for sCD14, and 0.39 (IQR, 0.32–0.47) for D-Dimers. There were no differences in biomarker reduction across treatment arms. Conclusions: In participants with HIV and TB, EFV, RAL400, or RAL800 effectively and equally reduced inflammation and HIV-1 DNA levels. Abstract : In antiretroviral-naive participants coinfected with HIV and TB and treated with rifampicin, EFV 600 mg QD or RAL400 or RAL800 mg BID had a similar effect on reducing HIV DNA and systemic inflammation in the first 48 weeks on therapy.